Quality: a contributing factor to become competitive and innovative / Mohd Zahid Laton - Laton, Mohd Zahid (2009)
People or even organisations emphasize on the quality which is the important thing requested by customers. seek. Customers are seeking seek quality in order to full-fill and satisfy their needs and wants which are non-limited in nature. This paper will discusses the concept of quality which is the a contributing factor to become competitive and innovative. Motivation, job satisfaction and performance will be explained in the quality context which is driven drives one to the be competitive and innovative personnel (something is needed here) in the business world. Quality is the never ending story and it will keep moving and improving from time to time in order order for an organisation to become relevant and significant. organization. (what to become relevant and significant?.